Optimization of Cotton Fabric Dyeing Using Urera Hypselodendron Leaf Extract and Wood Ash as a Bio-Mordant - Asnake Ketema; Li-Chun Chang; Wei-Yu Chen (Journal of Natural Fibers)
In recent years, natural dyes have gained importance in textile dyeing applications, as many synthetic dyes have been found to be carcinogenic, mutagenic, and allergenic. This study investigates the use of natural dyes derived from Urera hypselodendron leaves, in combination with wood ash as a bio-mordant, for dyeing cotton fabrics. Aluminum sulfate (5%) and iron (II) sulfate (1%) were used as control mordants for comparison with the ash-based mordant. For the dyeing process, three common mordanting techniques were applied: pre-mordanting, meta-mordanting, and post-mordanting. Pre-mordanting with aluminum sulfate resulted in the highest color strength and overall fastness properties. Using the pre-mordanting method, the ash-mordanted samples produced a dull yellowish color with uniform dye uptake, achieving a maximum color strength (K/S value) of 2.704. Process optimization was carried out by varying the dyeing parameters such as time (30–75 min), temperature (45–105°C), and dye concentration (2–6% o.w.f.). The optimal dyeing conditions included a mordant concentration of 4.99%, a dyeing time of 51.59 min, a dye amount of 37.75 mL, and a dyeing temperature of 72.25°C. These results aim to develop a sustainable and eco-friendly dyeing method suitable for textile industries seeking alternatives to conventional chemical-based processes.